Enhancing English reading skills and self-regulated learning through online collaborative flipped classroom: a comparative study - Wang, Ying (Frontiers in Psychology, 2023)
Introduction This research investigates the effectiveness of an online collaborative flipped classroom approach in enhancing English reading skills and self-regulated learning among Chinese English learners. Methods A total of 71 participants were divided into three instructional groups: traditional instruction (TI) group (n = 24), flipped instruction (FI) group (n = 22), and online flipped instruction (OFI) group (n = 25). The participants’ reading comprehension ability was assessed using the reading section of the IELTS exam. Self-Regulated Learning (SRL) strategy use was evaluated using a questionnaire, and weekly online quizzes assessed participants’ understanding of course materials. Online learning behaviors were examined by considering online log-on times. The instruction period lasted for 12 weeks, with pre-tests and post-tests conducted to measure progress. Results The results indicated that both the FI and OFI groups outperformed the TI group in terms of reading comprehension and self-regulated learning. Furthermore, the OFI students demonstrated superior online learning behaviors and objective performances compared to the FI students. Discussion These findings suggest that the integration of flipped and online instruction methods holds promise for improving English reading skills and enhancing self-regulated learning among Chinese English learners.